Impact of Globalization of Firms: Descriptive Study on Performance on Network Ability - Bhaumik, Amiya; Aun Law, Kian; Jiemiao, Fang; Raju, Valliappan (International Journal of Psychosocial Rehabilitation, 2020)
With the deepening of globalization, the world economy has gradually become a unified whole of organic links. It is no longer the patent of large multinational companies to conduct international operations and expand overseas markets. More and more small and medium-sized enterprises have also actively participated in the world economy and embarked on a unique international management road. From the traditional point of view, SMEs should operate overseas in a relatively slow and gradual manner, but a growing number of studies have shown that many SMEs have successfully internationalized since their inception or within a short period of time since their inception. The number of such companies has gradually increased since the 1990s, which has attracted the attention of many scholars and relevant government decision-making departments and called such companies global firms.